2021
DOI: 10.1007/s00018-021-03882-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical cues as master regulators of hematopoietic stem cell fate

Abstract: Hematopoietic stem cells (HSCs) perceive both soluble signals and biomechanical inputs from their microenvironment and cells themselves. Emerging as critical regulators of the blood program, biomechanical cues such as extracellular matrix stiffness, fluid mechanical stress, confined adhesiveness, and cell-intrinsic forces modulate multiple capacities of HSCs through mechanotransduction. In recent years, research has furthered the scientific community’s perception of mechano-based signaling networks in the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 229 publications
0
21
0
Order By: Relevance
“…Mechanical signals act as important influences on the fate of living organisms in a number of areas, including the circulatory system [ 143 ], neural tissue [ 144 ], tendon tissue engineering [ 145 ], periodontal tissue engineering [ 146 ], cartilage tissue engineering [ 15 ], and others. The effects of several mechanical forces on disease are specified below.…”
Section: Clinical Applications Of the Mechanical Environment Of Stem ...mentioning
confidence: 99%
“…Mechanical signals act as important influences on the fate of living organisms in a number of areas, including the circulatory system [ 143 ], neural tissue [ 144 ], tendon tissue engineering [ 145 ], periodontal tissue engineering [ 146 ], cartilage tissue engineering [ 15 ], and others. The effects of several mechanical forces on disease are specified below.…”
Section: Clinical Applications Of the Mechanical Environment Of Stem ...mentioning
confidence: 99%
“…Hematopoietic stem cells are able to perceive both soluble signals and biomechanical inputs, including fluid mechanical stresses, from their microenvironment and are emerging as critical mechano-regulators of hematopoiesis. 151 The beating of the heart subjects HSCs to constant hemodynamic forces. In mice, circulating HSCs can experience shear stress that exceeds 600 dyn per cm 2 in regions of the aortic walls.…”
Section: Microgravitymentioning
confidence: 99%
“…Recently, it was shown that YAP activation and the upregulation of YAP target genes are sensitive to cyclic stretch, and for the first time, a connection between biomechanical cues and YAP in determining HSC fate has been confirmed. 167 Kruppel-like factor 2, 168 basic leucine zipper, 151 and cAMP response element-binding protein 169 may all also serve as other crucial transcription factors whose expression reflects the onset of fluid shear forces and prompts HSC differentiation.…”
Section: Microgravitymentioning
confidence: 99%
“…Fluid shear stress is absent in static culture systems despite this parameter can affect the hematopoietic niche through paracrine signaling stimulation, e.g. through Yap-1, Piezo 1 ( Heck et al, 2020 ; Zhou et al, 2020 ; Li et al, 2021 ). Endothelial cells can convert FSS into a biochemical response for the neighboring cells, regulating cycling and quiescence of HSCs ( Roux et al, 2020 ).…”
Section: Biophysical Factorsmentioning
confidence: 99%